Revision of Juncaceae and Cyperaceae phylogeny based on cpDNA and nDNA - Brožová, Viktorie (Jihočeská univerzita, 2018)
The phylogeny of Juncaceae and Cyperaceae is still not fully understood. The morphology of this group is intricate and without clear homology, and molecular relationships are mostly studied on smaller parts of this large group of Monocots. Proper study is therefore needed. To obtain the most objective view on the phylogeny of these two families, we gathered data on 1174 taxa of rbcL, trnL-trnF, and ITS and analysed them by maximum parsimony, maximum likelihood, and Bayesian inference. Markers of cpDNA appeared much more useful than nDNA (ITS) due to the high rate of mutations in ITS which led to homoplasy and unsure alignment. By considering taxonomical impact of our study, the monophyly of the families and main inner topology of Juncaceae and several tribes of Cyperaceae (Abildgaardieae, Bisboeckelereae, Cariceae, Cypereae, Cryptangieae, Eleocharideae, Rhynchosporeae, Sclerieae, and Trilepideae) were confirmed; some changes in taxonomy were suggested (uniting of Chrysitricheae and Hypolytreae; division of Fuireneae; uniting of Cariceae, Dulicheae, Scirpeae, and Khaosokia caricoides into one tribe, or division of Scirpeae; and separation of Cladieae); changes in the classification of certain taxa were also suggested (the transfer of Distichia, Marsippospermim, Oxychloë, Patosia, and Rostkovia into Juncus, or division of Juncus into more genera; the transfer of Nemum spadiceum into Bulbostylis; Schoenoplectus corymbosus, S. gemmifer, S. hondoensis, and S. multisetus into the genus Schoenoplectiella; and Oreobolopsis into Trichophorum); and the identification of some taxa which possess special combinations of molecular and morphological features and should be studied further was made (Juncus capitatus, J. dregeanus, Bulbostylis juncoides, Crosslandia setifolia, Schoenoplectus litoralis, S. americanus, Cyperus iria, and Amphiscirpus nevadensis).
Revision of Juncaceae and Cyperaceae phylogeny based on cpDNA and nDNA
Keywords: phylogeny; Cyperaceae; Juncaceae; cpDNA; nDNA; phylogeny; Cyperaceae; Juncaceae; cpDNA; nDNA